PECULIARITIES OF CHEMIORESISTANT TUBERCULOSIS SPREAD IN TERNOPIL REGION IN RECENT YEARS - Vynnychuk, N.A.; Kymnyuk, S.I. (Інфекційні хвороби, 2015)
The article presents the results of the study of susceptibility of M. tuberculosis isolated from patients with pulmonary tuberculosis in 2007 to -2013 in the Ternopol region (Ukraine) The positive tendency of increasing the rate of susceptibility of M. tuberculosis anti-TB drugs in 2013 in comparison 2007 in patients with new tuberculosis and other cases of tuberculosis but not recidivation was marked in Ternopil region. In patients with new tuberculosis the number of pathogens which were susceptible to anti-TB drugs of the first line I for this period increased on 12,6%, while in patients with re-treatment of pulmonary tuberculosis, except recidivation - increased in 1,7 times, and in patients with of pulmonary tuberculosis relapses this index fluctuated between 27,1-47,6%. The relative amount of multiresistant strains during this period has deeply increased. Thus, in patients with new pulmonary tuberculosis twofold increase of the rate of multidrug-resistant strains in 2012 compared to 2010-2011 years was revealed. The same trend was observed in patients with tuberculosis recidivation. The attention was paid to the priority of the introduction of modern express methods of tuberculosis diagnosis and examination of susceptibility of its causative agents to antimycobacterial drugs. It will permit to correct antimycobacterial treatment in time, and reduce the number of relapses and appearance of chronic pulmonary tuberculosis in patients with multiresistant pathogens.